Phosphorescent oxygen-sensitive probes - Papkovsky, Dmitri B. (SpringerBriefs in Biochemistry and Molecular Biology, 2012)
Biological O2 sensing probes and measurement techniques were first introduced in the late 80s. In the last 3-5 years they have undergone major development that have made them available and affordable for a broad range of applications in various disciplines of the life and biomedical sciences. These new chemistries and technologies, which are significantly different from the majority of other fluorescence-based probes and detection techniques, have already demonstrated their high utility. This book will provide a systematic overview of the existing and emerging O2 sensing technologies in their different modifications, a practical guide to their rational selection and use, and examples of biological applications/case studies, including details on how to set up and conduct such experiments, troubleshoot and interpret the data.